La depresión en los pacientes adolescentes con acné del Bachillerato de los colegios: Tecnológico Fiscomisional Nuestra Señora del Rosario, Emiliano Ortega Espinosa y Unidad Educativa Municipal de Catamayo, en el periodo comprendido entre diciembre 2012 - mayo 2013. - Ayala Robles, Luis Eladio (2014)
The present study aims to determine the degree of depression in adolescents with acne in high school students aged between 15 and 18 years old of: “Nuestra Señora del Rosario Technical Institute”, Emiliano Ortega Espinoza, and Municipal High Schools of Catamayo city, in the period December 2012 - May 2013. It is a descriptive, transversal study, where the population is 883 students, of whom I chose a random sample of 400 students and applied a survey, a test, including a physical examination. Depressive symptomatology was assessed using the Beck Depression Inventory, Acne severity was assessed using The Global Acne Grading System (GAGS) of FDA. In addition, the survey recorded information corresponding to the objectives of investigation, as gender, age, acne severity, acne family history and if the affected students take medication and what is this medication. According to the results, found that in adolescents with acne, 43,67 percent had mild depression; 10,12 percent had moderate depression and a 6,32 percent had severe depression, in comparison with the adolescents who do not have acne, 18,18 percent had mild depression, 8,26 percent had moderate depression, and a 2,47 percent had severe depression. The gender most affected with acne, was the female gender (53,79%) being the most vulnerable to depression too. In the studied sample, the acne predominant degree was the mild acne, followed by the moderate and severe acne. Concerning with the family history acne is frecuently. A 38,6 percent was taking acne medication, while many of them didn´t remember it. Keywords: acne, depression, adolescence.